Exceptional performance of room temperature sputtered flexible thermoelectric thin film using high target utilization sputtering technique - Tao, X; Dutson, J; Zeng, C; Asker, C; Luong, S; Reza, A; Hao, B; Zhang, Z; Ellingford, J; Bonilla, RS; Fenwick, O; Bilotti, E; et al. (Wiley, 2024)
The High Target Utilisation Sputtering technique (HiTUS) is of interest for industrial processes, including in roll-to-roll manufacturing. This study marks the first application of HiTUS to thermoelectric materials, exemplified by bismuth telluride. The HiTUS technique separates the sputtering power into the plasma power and the target power, with additional kinetic energy in the sputtering particles from the applied electrical field, thus enabling a much wider sputter parameter space to modify the film performance. This study investigates how plasma power, target power, and substrate bias in HiTUS intricately influence crystal orientation/size, elemental composition, surface morphology, and other film properties. These factors subsequently affect carrier density/mobility, and consequently the thermoelectric performance of the bismuth telluride film. These deposited films reach a power factor of 6.5 × 10−4 W m−1 K−2 with a figure of merit ≈0.14 at room temperature, the highest value for room-temperature sputtered un-doped bismuth telluride. Subsequent post-deposition annealing significantly enhances the crystallinity of the film (highly polycrystalline), further improving the power factor to 23.5 × 10−4 W m−1 K-2, with a figure of merit ≈0.45 at room temperature. The excellent performance of the HiTUS fabricated thermoelectric film opens opportunities for the large-area manufacture of thin-film thermoelectric materials and devices.